2018
DOI: 10.1007/s12035-018-1090-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Brain Lysosomal Activities in GBA-Related and Sporadic Parkinson’s Disease and Dementia with Lewy Bodies

Abstract: Mutations in the GBA gene, encoding the lysosomal hydrolase glucocerebrosidase (GCase), are the most common known genetic risk factor for Parkinson's disease (PD) and dementia with Lewy bodies (DLB). The present study aims to gain more insight into changes in lysosomal activity in different brain regions of sporadic PD and DLB patients, screened for GBA variants. Enzymatic activities of GCase, β-hexosaminidase, and cathepsin D were measured in the frontal cortex, putamen, and substantia nigra (SN) of a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 57 publications
6
107
0
1
Order By: Relevance
“…Previously, we could show that PD patients carrying a GBA1 mutation (PD GBA ) also present reduced CSF levels of total alpha‐synuclein compared to PD patients with GBA1 wild type . Histopathological studies in PD and DLB report reduced GCase activity paralleled by alpha‐synuclein pathology in brains of GBA1 mutation carriers …”
Section: Discussionmentioning
confidence: 97%
“…Previously, we could show that PD patients carrying a GBA1 mutation (PD GBA ) also present reduced CSF levels of total alpha‐synuclein compared to PD patients with GBA1 wild type . Histopathological studies in PD and DLB report reduced GCase activity paralleled by alpha‐synuclein pathology in brains of GBA1 mutation carriers …”
Section: Discussionmentioning
confidence: 97%
“…To what extent CSF profiles of alpha‐synuclein might reflect the underlying pathology in the brain is unclear. Histopathological studies in PD report reduced GCase activity paralleled by alpha‐synuclein pathology in the brains of GBA1 mutation carriers . Following this mechanistic link between GBA1 mutations and alpha‐synuclein, it is tempting to speculate whether the reduced CSF levels of total alpha‐synuclein observed in the PD patients with severe GBA1 mutations might reflect alpha‐synuclein accumulation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies in PD report reduced GCase activity paralleled by alpha-synuclein pathology in the brains of GBA1 mutation carriers. [16][17][18] Following this mechanistic link between GBA1 mutations and alpha-synuclein, it is tempting to speculate whether the reduced CSF levels of total alpha-synuclein observed in the PD patients with severe GBA1 mutations might reflect alpha-synuclein accumulation in the brain. In this line of evidence, larger cohort studies in PD report total CSF levels of alpha-synuclein to be decreased with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced GCase activity was also found in the cingulate cortex of PD patients without GBA1 mutations . Moors and colleagues found significantly decreased GCase activity in the SN of both PD and DLB patients; a similar, though not significant, trend was also observed in the frontal cortex and putamen. In this series, CTSD activity was significantly decreased in the frontal cortex of DLB and PD patients, both in GBA1 mutation carriers and noncarriers.…”
Section: The Issue Of Alp Alterations In Sporadic Pdmentioning
confidence: 88%
“…In brain tissue, GCase activity and content have been shown to be reduced in the SN and other brain regions in different studies, both in GBA1 mutation carriers and sporadic PD patients . Importantly, Murphy and colleagues showed that the reduced activity is more evident at the early PD stage, and that the brain regions in which GCase activity is most affected are also those in which α‐syn accumulates the most.…”
Section: The Issue Of Alp Alterations In Sporadic Pdmentioning
confidence: 99%